Plan Colombia: Exploring some myths and effects on Colombian foreign policy 1998-2006 (2009)
The internationalization of Colombian conflict with the setting up of Plan Colombia by Andrés Pastrana, then maintained by Álvaro Uribe, increased foreign policy fragmentation and confusion in the conduct of the country's foreign relations. Three arguments are analyzed: first, Plan Colombia intensified the presidential conduct of diplomatic relations and the fragmentation of foreign relations, and made the role of the Foreign Ministry weaker than before. Second, Plan Colombia made relations with USA more complex and diminished and to some extent worsened Colombia's relations with the European Union and most of its members. And finally, Plan Colombia stimulated the international participation of non-state actors, especially non-government organizations, who started to do a parallel diplomacy in Washington and in Brussels. The presidency of Andrés Pastrana and the first presidency of Álvaro Uribe will be examined within the geographic triangle of Colombia, the USA and Europe.